Everyday surveillance vigilance and visibility in postmodern life - Staples, William G. (Rowman & Littlefield, 2014)
When we think of surveillance in our society, we usually imagine "Big Brother" scenarios with the government tracking our every move. The actual surveillance of our everyday lives is much more subtle, however, and may be more insidious. William G. Staples shows how our lives are tracked by both public and private organizations --sometimes with our consent, and sometimes without--through our internet use, cell phones, public video cameras, credit cards, license plates, shopping habits, and more. Everyday Surveillance is a provocative exploration of the myriad ways we are watched each day, and how this surveillance shapes our lives. Thoroughly revised, the second edition considers new topics, such as the rise of social media, and updates research throughout. Everyday Surveillance introduces students to concepts of social control and incites classroom discussion about how surveillance impacts the ways we understand people and our lives at home, work, school, or in the community.